Profile of Patients of Hepatocellular Carcinoma in The Internal Medicine Inpatient Room at Dr. Soetomo General Academic Hospital - Shahnaz Azzahra; Ulfa Kholili; Rosy Setiawati; Ummi Maimunah (Universitas Airlangga, 2023)
Introduction: Primary liver cancer is the sixth most frequently diagnosed cancer and the third leading cause of cancer death worldwide in 2020, with approximately 906,000 new cases and 830,000 deaths. Primary liver cancer includes hepatocellular carcinoma (HCC), with a percentage of 75%-85% of cases. The poor prognosis of HCC is mainly related to late diagnosis.Methods: This research is a descriptive study with a cross-sectional study. Data retrieval is taken from secondary data in the form of medical record data. The sampling technique used was the total sampling technique.Results: The number of HCC patients in the Internal Medicine Inpatient Room at Dr. Soetomo General Academic Hospital for 1 January 2017–31 December 2019 who met the inclusion and exclusion criteria was 60. The male sex had the highest number of 43 patients (71.7%), with the highest age group being 50-59 years old.Conclusion: Profile of HCC patients in the Internal Medicine Inpatient Room at Dr. Soetomo General Academic Hospital for the 2017-2019 period, the largest age group was 50-59 years, dominated by male sex, the most risk factors were HBsAg positive, high liver function tests, high tumor markers, and had BCLC stage C. The patient had a live clinical outcome.